Hiscock, Benjamin St. Clare. Interview about life in Champney's West, NL. - Barrett, Terra; Jarvis, Dale (2015)
Interview with Benjamin Hiscock of Champney's West, NL about growing up in the community, ship wrecks, local characters, and square dancing. Ben Hiscock from Champney’s West, Trinity Bay, NL describes how his father met his mother; 00:39 – Hiscock describes his father’s work; Hiscock names his grandparents; 1:12 – Hiscock was born on December 2nd, 1942 and Hiscock explains his name Benjamin St. Clare Hiscock and where it came from; 2:07 – Hiscock describes growing up in Champney’s West and how supportive the community was; Changes in the community – television, population, hydro, plumbing, telephone; Question of what will happen in the community once the senior citizens pass away; Need for something to keep the community going; 5:01 – Hiscock describes an early memory of growing up in Champney’s West and hammering a penny to close the hole in the penny in order to buy a ginger snap at the shop owned by Mr. Myer Goldsworthy; 7:42 – Hiscock describes fishing with his father; Fishing grounds; Hand lining and trawls; 9:16 – Hiscock describes changes in the fishery in Champney’s West with new technology and regulations; 11:45 – Keeping up the fishing stages; 12:22 – Change in visiting in the community; 13:01 – Hiscock describes the shipwreck of the Saladin on December 28, 1943; An older man went outside to use the washroom and heard people screaming; Local man made a bosun’s chair; Community men rescued the people from the Saladin; Local man, Wilfred Hiscock who jumped out on the rock to save the men; 18:27 – Hiscock describes a bosun’s chair and the captain of the Saladin; 19:45 – Hiscock describes the shipwreck of the Hazel Pearl on February 28, 1944; Hazel Pearl hit the hard ice and sunk; Hiscock describes how Wayne a local man salvages the spar from the Hazel Pearl; 22:10 – Hiscock describes other shipwrecks in the area such as the Mayflower; 22:38 – Hiscock tells the story of the person buried on Fox Island; Describes how his family settled Fox Island; Hiscock suspects the body found in the bog on Fox Island ...